Risk factors and the outcome of therapy in patients with seizure after Carbamazepine poisoning: A two-year cross-sectional study - Ahmad Yaraghi; Nastaran Eizadi-Mood; Marzieh Salehi; Gholamreza Massoumi; Lejla Zunic; Ali Mohammad Sabzghabaee (Wolters Kluwer Medknow Publications, 2015)
Objective: We aimed to investigate the frequency of seizure after acute carbamazepine poisoning and the important risk factors related to the outcomes of therapy. Methods: In this two-year cross-sectional study conducted in a University Hospital in Iran, 114 patients with acute carbamazepine poisoning were divided into two groups of with seizure (n = 8) and without seizure (n = 106) after intoxication. Demographic data, average amount of drug ingestion, time elapsed from ingestion to hospital admission, history of seizure before poisoning, mental status, visual disturbances and nystagmus, duration of hospitalization, the outcomes of therapy, arterial blood gas values and serum biochemical indices were compared between the two groups. Findings: Patients with seizure had an estimated (Mean ± SD) ingestion of 14,300 ± 570 mg carbamazepine, which was significantly higher (P < 0.0001) than the seizure-free group (4600 ± 420 mg). The estimated average time between drug ingestion and hospital admission in patients with seizure and the seizure-free group were 515 ± 275 and 370 ± 46 minutes, respectively (P < 0.0001). In this study, 104 out of the total number of patients had recovered without any complication. Need for respiratory support, including airway support or intubation were the most recorded complication. One patient died after status epilepticus and aspiration pneumonia. Conclusion: The ingested amount of carbamazepine and the time elapsed from the ingestion of drug to hospital admission may influence the occurrence of seizure after acute carbamazepine poisoning; however, the outcome of supportive care in these patients seems to be positive.